Epidemiological Surveillance of Communicable Diseases in Baghdad City during the Period January-April 2006 (Baghdad Science Journal, 2025)
The records of Primary Health Care Centres (Al-Risafa section of Baghdad) were inspected for communicable diseases during the period January-April 2006. There were 8622 recorded cases (the diagnosis was based on a clinical examination and laboratory findings), which were distributed as 4782 (55.5%), 1430 (16.6%), 1604 (18.6%) and 806 (9.3%) for Sadar city, Risafa, A'adhamyiah and Mada'in, respectively. The highest frequency was reported for chicken pox (42.7%), followed by mumps and typhoid fever (20 and 13.7%, respectively), while diphtheria and cholera were not recorded. These three most frequent diseases were further analyzed, and their distribution showed a significant difference (P ? 0.001). April was the month of the highest recorded cases (48.05%), followed by March (18.8%), January (18.1%) and finally February (14.7%).